Cruise Tourism in the Caribbean Selling Sunshine - Honey, Martha (USA; Routledge, 2019)
This book considers the limited economic benefits of cruise tourism, its environmental and social impacts, and the effects of climate change, and "overtourism." Based on this analysis and case studies of key Caribbean and Mediterranean destinations, this book cautions against overdependence on cruise tourism and outlines reforms needed to bring more benefits and equity to Caribbean countries. It will be valuable to professionals, businesses, development agencies, NGOs, and academics interested in a sustainable cruise industry and the economic well-being of Caribbean island nations.
English
Keywords: 21st century; G154.9-155.8 Travel and state. Tourism; Caribbean